DEFENSIVE MEDICINE AS A RESULT OF MEDICAL NEGLIGENCE : A BRIEF OVERVIEW - Rozlinda Mohamed Fadzil; Asma Hakimah Abd Halim; Ain Alya Ariffin (UNTAG Law Review, 2018)
Medical negligence is a topic in tort law which has been widely discussed as good, affordable healthcare, is greatly related to a nation’s proof of its valiant efforts to attain a developed nation from a developing status by providing state of the art health care available and affordable, to all levels of society. As a penalty in medical negligence, damages are met out to punish errant members of the medical fraternity by way of legal judgements in a court of law. In some circumstances members of the medical fraternity may also have their medical licenses suspended or revoked. Annually, medical negligence’s claim rates are inherently high and are expected to rise in tandem with patients’ awareness of their medical rights. Complication arises when the plaintiff in a medical negligence law suit face difficulties in trying to prove that the negligence really did occur. In obtaining access to medical records after a purported civil malpractice accusation, obstruction of justice is rife. They arise when blurred lines cross between obligation of doctor-patient confidentiality and the need to disclose patient’s medical records in order to securely obtain accurate sworn testimony of other medical practitioners. It is on the shoulders of the plaintiff, which in most medical malpractice law suits, rests on the patient (patients to the defendant doctors), to prove on a balance of probabilities that the breach of the duty of care did occur and from that breach, negligence had emerged, bringing about the claimed harm resulting in inherent damages suffered. High cost of litigation is also a common effect in medical malpractice law suits. This inevitably raises the insurance premium costs of all medical professionals, in general. These factors serve as impediments towards the plaintiff in obtaining justice. Hence, this paper will try to analyse the causes that has led to some of these problems. Also what will be the undesired effect caused by the difficulties in trying to prove that a medical malpractice has indeed occurred? The initial hypothesis to the matter is that it will cause negative effects to the livelihood of a patient’s life and seriously hider access to medical care. This paper will however only be focusing on one popular but ill-favouredeffect that is greatly deliberated on when medical negligence is discussed, which is defensive medicine. Defensive medicine is actually a reaction culminating from the fear of medical malpractice lawsuits by medical practitioners. Fear of facing or being taken action upon, has caused them to take necessary safe steps which is to practice defensive medicine to avoid such risk.